Essays on Mesopotamian Civilization. Selected Papers of A. Leo Oppenheim - Reiner, Erica
Microfiche edition, 9 fiches (each = ca. 90 p.); reprinted articles on I. Cultural History, II. Social History, III. Science and Technology, IV. Religion, V. Linguistics; Bibliography of Works by A. L. Oppenheim.